Floating Market Resort Danau Koto Panjang Dengan Pendekatan Ekowisata - Ayu Riska Putri; Pedia Aldy; Muhammad Rijal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Koto panjang has many potential that could be developed. However, many potential faded because it doesnt really exposed, one of local potential that could be developed even more is Koto Panjang’s lake region hydroelectricity (PLTA). Location in Merangin village, Kampar regency, Riau, has a beautiful natural scenery. Clean environtment, and quite. This is very suitable for a resort, holiday and also a new touris attraction that could be developed, aside as a hydroelectricity to Riau society, based on the number on problem to desain a facility that acomodatete a resort activity and holiday also tourist attraction to Riau society with presented resort and Floating Market. That abuse local potential that exist such as Koto Panjang’s lake region hydroelectricity (PLTA), this floating market built in 3,3 ha on 4,3 ha on ground built area koto panjang’s lake Floating Market made with eko excursion approach that notice balance of nature environtment and artificial environtment. Ecoturism is a road tour activity with developed local potential in the design of this Floating Market Resort lake on concept that combined tradisional houses of kampar’s elements taken from ecotourism element.Keywords: Floating Market Resort, Ecotourism, Kampar